P300-based brain-computer interface communication: evaluation and follow-up in amyotrophic lateral sclerosis - Silvoni, Stefano; Volpato, Chiara; Cavinato, Marianna; Marchetti, Mauro; Priftis, Konstantinos; Merico, Antonio; Tonin, Paolo; Koutsikos, Konstantinos; Beverina, Fabrizio; Piccione, Francesco (Frontiers in Neuroscience, 2009)
Objectives: To describe results of training and one-year follow-up of brain-communication in a larger group of early and middle stage amyotrophic lateral sclerosis (ALS) patients using a P300-based brain-computer interface (BCI), and to investigate the relationship between clinical status, age and BCI performance. Methods: A group of 21 ALS patients were tested with a BCI-system using two-dimensional cursor movements. A four choice visual paradigm was employed to training and test the brain-communication abilities. The task consisted of reaching with the cursor one out of four icons representing four basic needs. Five patients performed a follow-up test one year later. The clinical severity in all patients were assessed with a battery of clinical tests. A comparable control group of 9 healthy subjects was employed to investigate performance differences. Results: 19 patients and 9 healthy subjects were able to achieve good and excellent cursor movements’ control, acquiring at least communication abilities above chance level; during follow-up the patients maintained their BCI-skill. We found mild cognitive impairments in the ALS group which may be attributed to motor deficiencies, while no relevant correlation has been found between clinical data and BCI performance. A positive correlation between age and the BCI-skill in patients was found. Conclusion: Time since training acquisition and clinical status did not affect the patients brain-communication skill at early and middle stage of the disease. Significance: A brain communication tool can be used in most ALS patients at early and middle stage of the disease, before entering the locked-in stage.